Gender and social class inequalities in higher education: intersectional reflections on a workshop experience - Fernandez, Daniela; Orazzo, Emily; Fry, Emma; McMain, Alice; Ryan, Michelle K.; Wong, Chuk Yan; Begeny, Christopher T. (Frontiers in Psychology, 2024)
Research about the experiences of underrepresented groups in higher education (HE) demonstrates the persistence of challenges, despite policies and institutional strategies to promote inclusion. Diversity and inclusion policies have been part of the HE agenda for several decades, yet most policies and interventions focus on (a) a given, isolated identity experience (e.g., based solely on gender, social class, or ethnicity) rather than more intersectional approaches to identity; and (b) top-down interventions that do not include participants insights in their design. We aimed to explore these challenges by creating a workshop with students at an elite university that drew on an intersectional approach to social identities (IASI), specifically, looking at gender and social class. We report a case study of this workshop and analyse some of the opportunities and challenges that this method entails. We explore four key themes: (a) the importance of group processes, (b) the use of visual techniques, and (c) the institutional tensions and the (de)politicisation of social psychology research. Reflecting on this case study we argue that approaches to identity and inclusion in HE can benefit from intersectionality beyond the use of multi and overlapping identity and social group categories. We argue that research in this space is not neutral and needs to acknowledge researchers' position about (a) inclusion and diversity, (b) perceptions of participants in research, and (c) the motivation and aims of institutions where the research is conducted. Finally, we discuss the theoretical and practical implications of integrating an intersectional approach within social identity research in HE when focusing on underrepresented groups.